Metagenomic Analysis Identified Stenotrophomonas maltophilia Pneumonia in an Infant Suffering From Unexplained Very Severe Pneumonia - Lin, Yan; Wang, Bao-Xi; Zhang, Ni-Ni; Zhang, Lei; Gao, Zhi-Bo; Tian, Jiao; Jiang, Xun (Frontiers in Pediatrics, 2019)
Pneumonia poses a significant global morbidity and mortality burden on children. Etiological diagnosis and matched anti-microbial therapy are particularly important for very severe pneumonia. Although great advances have been achieved in diagnostic approaches, it remains challenging to identify pathogens in unexplained pneumonia (UP) cases. In this study, we applied next-generation sequencing (NGS) technology and a metagenomic approach to detect and characterize respiratory bactiera in an UP case in infant. Stenotrophomonas maltophilia was the only bacterial pathogen detected in blood. Metagenomic sequencing also provided bacteria genomic sequences, which could be used to evaluate the role of this pathogen in the disease. This NGS method has the potential to improve the identification of causative organisms in patients with pneumonia and the delivery of appropriate, pathogen-directed antibiotic therapy.